2020
DOI: 10.3390/ijms21113861
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Proatherogenic Cytokine Levels

Abstract: Background: It has been shown that sex affects immunity, including cytokine production. Given that atherosclerosis is an inflammatory disease promoted by specific cytokines, such as interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α, we aimed at evaluating whether sex could affect the levels of these proatherogenic cytokines in a group of healthy adults. In this analysis, we also included other cytokines and peptides that have been implicated in atherosclerosis development and progression. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 46 publications
8
26
0
Order By: Relevance
“…Results from previous studies demonstrated sex differences in levels of some cytokines among young adults (median age = 22 years) [41], and in cytokine secretion responsiveness of lymphomonocytes under stress conditions [42]. We found nonsignificant differences of cytokine levels (data not shown, p > 0.10) and similar reproducibility of cytokines between older males and females in this study, which might be due to the depletion of sex steroid hormones in elderly subjects.…”
Section: Discussionsupporting
confidence: 57%
“…Results from previous studies demonstrated sex differences in levels of some cytokines among young adults (median age = 22 years) [41], and in cytokine secretion responsiveness of lymphomonocytes under stress conditions [42]. We found nonsignificant differences of cytokine levels (data not shown, p > 0.10) and similar reproducibility of cytokines between older males and females in this study, which might be due to the depletion of sex steroid hormones in elderly subjects.…”
Section: Discussionsupporting
confidence: 57%
“…20 In addition, the 20 In relation to the body of literature, the mortality rate observed in our study was slightly higher than rates seen in other settings such as China and Italy. [20][21][22][23] Our data suggested that the mortality rate among male Brazilian subjects was higher than the rate among females. This had also been observed in previous studies.…”
Section: Discussionmentioning
confidence: 82%
“…Initially, it was suggested that women might be less susceptible to viral infections than men due to higher production of circulating antibodies along with prolonged levels of these biomarkers. 22,23 Additionally, another factor that might explain the lower susceptibility of female patients to the novel coronavirus infection is their production of estrogen and immune factors linked to X chromosomes. 24 In women, the double X chromosome affects the immune system with regard to expression of several elements, such as the expression of toll-like receptor 7 (TLR7).…”
Section: Discussionmentioning
confidence: 99%
“…However, a significantly higher ACE2 serum activity was observed in women older than 55 years old compared to women younger than 55 years with no significant difference in serum ACE2 activity between older and younger men. Bernardi et al 21 also found no difference in ACE2 serum level between healthy men and women. In a recently published study in patients with heart failure, defined as left ventricular ejection fraction of ≤40% or plasma concentrations of B-type natriuretic peptide and/or N -terminal pro-brain natriuretic peptide >400 pg/mL or >2000 pg/ml, respectively, serum level of ACE2 was higher in men than in women.…”
Section: Sex-associated Differences In Circulating Ace2 Activitymentioning
confidence: 90%